PROSPECTS FOR THE USE OF METAL OXIDES IN NANOFORM FOR INDUSTRIAL WASTEWATER TREATMENT - Kochubei, Olena; Sovhira, Svitlana; Dushechkina, Nataliia (Water and Water Purification Technologies. Scientific and Technical News, 2025)
The article presents the results of a theoretical study on the prospects for the use of metal oxides in nanoform for industrial wastewater treatment. The growing problem of water pollution by inorganic compounds, especially heavy metals (Pb²⁺, Cd²⁺, Hg²⁺, Cr⁶⁺), as well as phosphates, nitrates, and sulfates, creates a demand for innovative and eco-friendly purification technologies. Conventional treatment methods often lack effectiveness under conditions of high pollutant concentrations or complex wastewater composition. Nanostructured metal oxides, due to their high surface area, ion-exchange capacity, and catalytic activity, offer promising solutions for pollutant removal. The study provides an analytical overview of recent scientific literature on the properties, synthesis methods, and application of TiO₂, ZnO, Fe₃O₄, MnO₂, CuO, and Al₂O₃ in purification processes. The mechanisms of sorption, photocatalysis, precipitation, and complexation are discussed in detail. Influencing factors such as pH, particle morphology, temperature, pollutant concentration, and contact time are analyzed. Special attention is paid to the development of composite materials and surface-functionalized nanomaterials, which enhance selectivity, reusability, and stability in aggressive environments. The potential environmental impact, regeneration strategies, and barriers to large-scale application are also considered. The conclusions highlight the relevance of nanostructured metal oxides in the development of efficient, scalable, and sustainable technologies for water purification, in line with modern ecological and industrial challenges. Further interdisciplinary research is recommended to address safety, standardization, and cost-effectiveness aspects.